Data Collecting and Research of Folk Medicine in Estonia During the Soviet Era - Ave Tupits (Journal of Ethnology and Folkloristics)
Folk medicine in Estonia has been studied more thoroughly within the last 30 years. Still, the respective data has always been on the folklorists’ work-list, when publishing questionnaires or going out on fieldwork. It has to be taken into consideration that the times were hard for folkloristics both during the Soviet occupation in 1940–1941 and the German occupation in 1941–1944. Also the new political situation had its demands on scholarly research throughout the second Soviet occupation in the years 1945–1991. Nevertheless, by far the biggest collection campaign of Estonian folk medicine took place in 1959. Focused interest of folklorists in this topic grew significantly in the 1970s and 1980s, the last decades of the Soviet era, when official access to folk healers was allowed and New Age phenomena spread. The article is an abridged version of a chapter in an upcoming doctoral dissertation analysing the collecting and research of folk medicine in Estonia in the 20th century.